Solar photocatalytic reduction of Cr(VI) over Fe(III) in the presence of organic sacrificial agents - Belisa A. Marinho (2016)
Toxic hexavalent chromium reduction to less toxic trivalent chromium was evaluated using a solar driven photocatalytic system, Fe(III)/UV, in the presence of organic sacrificial agents. The photocatalytic reduction experiments were conducted in a lab-scale tubular photoreactor with compound parabolic collectors under simulated solar radiation. The effect of parameters such as iron (1-12 mg L-1) and citric acid (0.058-3.840 mM) concentrations, pH value (3.0-8.0), temperature (15-40 degrees C), UVA irradiation source and initial Cr(VI) concentration (1, 10, 20, 40 mg L-1) on the process efficiency was analyzed, and also the addition of other organic ligands like oxalic acid, maleic acid and EDTA. The presence of citric acid proved to enhance the Cr(VI) reduction by Fe(III)/UV due to the formation of Fe(III)-Citrate complexes, providing a quicker pathway for ferric iron regeneration in the presence of UV-vis light. The organic ligands proved to act also as sacrificial agents of reactive oxygen species formed, avoiding the Cr(III) re-oxidation. The catalytic activity of the organic ligands in the Cr(VI) reduction by Fe(III)/UV followed this order: citric acid > oxalic acid > EDTA > maleic acid. The best Cr(VI) reduction (99% in 15 min) was achieved with citric acid in a Cr(VI):Citric acid molar ratio of 1:3 at pH 5 and 25 degrees C. Finally, the photocatalytic reduction of Cr(VI) present in a real effluent was achieved after 30 min, demonstrating the potential of the Fe(III)/UVA-vis/citric acid system for the treatment of Cr(VI) containing wastewaters.